Late Quaternary clay mineral assemblages in the Western Pacific Warm Pool - Jiawang Wu; Zhifei Liu; Chao Zhou (PANGAEA, 2022)
Clay mineralogy data of late-Quaternary marine sediment cores in the western equatorial Pacific are presented here. These include core KX21-2 collected on the Ontong Java Plateau (downcore profile over the past 380 ka), as well as cores KX10-1, KX12-1, KX13-1 and KX15-2 collected off the northern coast of Papua New Guinea (surface samples only). All the five cores were retrieved a giant gravity corer onboard R/V Kexue-1 during the KX08-973 cruise in 2008/2009.